INOVASI PELAYANAN ADMINISTRASI ANAK LAHIR PULANG BAWA AKTE ( ALPUKAT) DI KOTA PALU - Nasrullah; Rusmawaty Bte. Rusdin (Journal Publicuho, 2025)
This study aims to determine the Innovation of Birth Certificate Administration Services (Avocado) in Palu City. This study uses a qualitative descriptive research methodology. The data for this study came from two sources: primary data collected through extensive interviews with related informants and secondary data taken from related documents. Data collection methods include observation, interviews, and documentation. The results of the study indicate that birth certificate services with the ALPUKAT program are still not optimal. Applicants from the general public or those specifically looking for birth certificates, as well as service counter officers, are all stakeholders in birth certificate service innovations that aim to expedite the application process and provide the best service to the community. There must be a solid legal basis, support from program implementers, increasing awareness of the complex demands of society, and good public perception of bureaucratic services so that innovation can develop in birth certificate services. Many things hinder innovation in birth certificate services, such as a lack of public knowledge about service needs, few birth certificate service counters, and few opportunities for employees to pursue skills and career training.